Dipeptidyl peptidase 4 inhibitor sitagliptin decreases myocardial fibrosis and modulates myocardial insulin signaling in a swine model of chronic myocardial ischemia. - Dwight D Harris; Sharif A Sabe; Mark Broadwin; Chris Stone; Krishna Bellam; Akshay Malhotra; M Ruhul Abid; Frank W Sellke (PLoS ONE, 2024)
Although both clinical data and animal models suggest cardiovascular benefits following administration of Dipeptidyl Peptidase 4 (DPP-4) inhibitors, the underlying mechanisms remain unclear. We therefore sought to evaluate the effect of the DPP-4 inhibitor sitagliptin on myocardial fibrosis, and insulin signaling in chronic myocardial ischemia using a swine model. An ameroid constrictor placement on the left coronary circumflex artery of thirteen Yorkshire swine to model chronic myocardial ischemia. After two weeks of recovery, swine were assigned to one of two groups: control (CON, n = 8), or sitagliptin 100mg daily (SIT, n = 5). After 5 weeks of treatment, the swine underwent terminal harvest with collection of myocardial tissue. Fibrosis was quantified using Masson's trichrome. Protein expression was quantified by Immunoblotting. Trichrome stain demonstrated a significant decrease in perivascular and interstitial fibrosis in the SIT group relative to CON (all p<0.05). Immunoblot showed a reduction in Jak2, the pSTAT3 to STAT 3 Ratio, pSMAD 2/3, and SMAD 2/3, and an increase in STAT 3 in the SIT group relative to CON (all p<0.05). SIT treatment was associated with increased expression of insulin receptor one and decreased expression of makers for insulin resistance, including phospho-PKC- alpha, RBP-4, SIRT1, and PI3K (p<0.05). Sitagliptin results in a reduction in perivascular and interstitial fibrosis and increased insulin sensitivity in chronically ischemic swine myocardium. This likely contributes to the improved cardiovascular outcomes seen with DPP-4 inhibitors.